Cryptocurrencies as a tool accelerating the process of globalisation - Majewski, Marcin (Kryptowaluty jako narzędzie przyspieszające proces globalizacji, 2019)
This article is about the process of globalisation supported by cryptocurrencies. It discusses the influence of cryptocurrencies on three major aspects: the political, economic and social spheres. The section on the political sphere highlights the way the authorities of some countries react towards cryptocurrencies. The evolving legal status of cryptocurrency in different regions is described. The section on the economic sphere enumerates examples of cryptocurrencies used on the financial markets. It shows how cryptocurrency might be used by the business sector. The social sphere section illustrates the major kinds of internet societies which are created around cryptocurrencies and what tools are facilitating cryptocurrency transfers. Many examples of important cryptocurrencies are used. The analysis of statistical data and literature have been used in order to evaluate the topic. The study provides additional evidence proving that cryptocurrencies have a significant impact on the process of globalisation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 7-18
Keywords: bitcoin; cryptocurrency; globalization; kryptowaluty; globalizacja